sheet

JP2025036163APending Publication Date: 2025-03-14TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024129653
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-06
Publication Date
2025-03-14

Smart Images

  • Figure 2025036163000002
    Figure 2025036163000002
  • Figure 2025036163000001
    Figure 2025036163000001
Patent Text Reader

Abstract

To provide a sheet that has high radio wave transmissivity and metal glossiness, and can reduce a variation in a color tone in a large area when viewed obliquely.SOLUTION: A sheet is such that, average reflectance of light in a wavelength range of 400-750 nm is 40-80% or less when the light is incident perpendicularly on a surface, and when color tone values are defined as a*[X°] and b*[X°], which are calculated by a calculation formula defined in JIS Z 8781 (2013) by using spectral reflectance measured at an incident angle X° relative to a perpendicular direction of the surface of the sheet, for a*[60°] and b*[60°] measured and calculated at 25 centers of square areas obtained by dividing a 50 cm by 50 cm sheet equally into 25 pieces, a difference Δa*[60°] between a maximum value and a minimum value of a*[60°], and a difference Δb*[60°] between a maximum value and a minimum value of b*[60°] satisfy following formulas (i) and (ii), respectively. (i) Δa*[60°]≤5.0. (ii) Δb*[60°]≤4.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet having a metallic luster. [Background technology]

[0002] Metallic gloss-like sheets are used to decorate the surfaces of various products such as home appliances, smartphones, and automobiles because they can provide a high-quality design, but with the recent spread of IoT and autonomous driving technology, there is a demand for metallic gloss-like sheets that are transparent to radio waves used in sensors for communication and autonomous driving. One example of a metallic gloss-like material that is transparent to radio waves is a laminated film in which hundreds of resin layers with different refractive indexes are laminated in a regular arrangement to reproduce the appearance of a metallic gloss-like texture through interference reflection.

[0003] Since the laminate structure of such a laminate film greatly affects its optical properties, if there is unevenness in thickness, it is likely to cause color variation, and color variation is particularly noticeable when viewed from an oblique angle. On the other hand, there is a demand for metallic glossy laminate films that have radio wave transparency and little color variation even when viewed from an oblique angle over a large area, for decorative applications such as mirror displays and grilles for electric vehicles.

[0004] Methods for suppressing color variation when such laminated films are viewed at an angle include a method of adjusting the thickness profile of the laminated structure to make any thickness unevenness less noticeable (Patent Document 1), and a method of suppressing color variation by adjusting reflected light by providing an appropriate coating layer (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 163891 [Patent Document 2] JP 2019-155621 A [Patent Document 3] JP 2016-066063 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the method described in Patent Document 1 produces a laminated film that is a polarizing film and does not produce a metallic gloss film that can be used for decorative purposes. The method described in Patent Document 2 limits the color tone variation that can be suppressed to red, making it difficult to provide a metallic gloss laminated film that can be used for large-area decorative purposes. Therefore, the present invention aims to provide a sheet that has high radio wave transmittance and metallic gloss, and can reduce color tone variation when viewed obliquely even over a large area. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention employs the following means. (1) The average reflectance of visible light from 400 nm to 750 nm when incident perpendicularly to the sheet surface is 40% or more and 80% or less, and the color tone value calculated by the formula specified in JIS Z 8781 (2013) using the spectral reflectance measured at an incidence angle of X° to the perpendicular direction of the sheet surface is a * [X°], b * When [X°] is set, a 50 cm square sheet is divided into 25 equal 10 cm squares, and the 25 points at the center of each square are measured and calculated. * [60°] and b * For [60°], a * Difference between maximum and minimum values ​​of [60°] Δa * [60°], and b * Difference between maximum and minimum values ​​of [60°] Δb * [60°] satisfies the following formulas (i) and (ii), respectively. Formula (i) Δa * [60°]≦5.0 Formula (ii)Δb * [60°]≦4.0 (2) a *Difference between maximum and minimum values ​​of [30°] Δa * [30°], and b * Difference between maximum and minimum values ​​of [30°] Δb * The sheet according to (1), wherein [30°] satisfies the following formulas (iii) and (iv), respectively. Formula (iii) Δa * [30°]≦4.5 Formula (iv)Δb * [30°]≦4.0 (3) A sheet according to (1) or (2), which is made by laminating two or more films, at least two of the films having a layer (A layer) mainly composed of thermoplastic resin A and a layer (B layer) mainly composed of thermoplastic resin B other than thermoplastic resin A, the A layer and the B layer being alternately positioned in the thickness direction, the total number of the A layers and the B layers being 499 or more, the sheet having three or more thick film layers having a thickness of 1 μm or more and 20 μm or less, and the thick film layers being the outermost layers on both sides. (4) The sheet according to (3), wherein the layer A and the layer B each contain a crystalline resin. (5) The sheet according to (4), wherein the proportion of the crystalline resin in all components constituting the A layer is more than 15% by mass and 100% by mass or less, and the proportion of the crystalline resin in all components constituting the B layer is 15% by mass or more and 75% by mass or less. (6) A laminate obtained by laminating a layer containing a polycarbonate resin as a main component onto the sheet according to any one of (1) to (5). Effect of the Invention

[0008] According to the present invention, it is possible to provide a sheet that has high radio wave transmittance and metallic luster, and is capable of reducing color variation when viewed obliquely even over a large area. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing one embodiment of a film constituting a sheet of the present invention (a diagram in which the thickness of layer A and the thickness of layer B are plotted against the layer number in a film in which layers A and B are alternately laminated in the thickness direction). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The sheet of the present invention has an average reflectance of 40% or more and 80% or less for visible light from 400 nm to 750 nm when incident perpendicularly to the sheet surface, and a color tone value calculated by the formula specified in JIS Z 8781 (2013) using the spectral reflectance measured at an incidence angle of X° relative to the perpendicular direction of the sheet surface is a * [X°], b * When [X°] is set, a 50 cm square sheet is divided into 25 equal 10 cm squares, and the 25 points at the center of each square are measured and calculated. * [60°] and b * For [60°], a * Difference between maximum and minimum values ​​of [60°] Δa * [60°], and b * Difference between maximum and minimum values ​​of [60°] Δb * [60°] respectively satisfy the following formulas (i) and (ii): The sheet of the present invention will be specifically described below. Formula (i) Δa * [60°]≦5.0 Formula (ii)Δb * [60°]≦4.0.

[0011] From the viewpoint of design, the sheet of the present invention must have an average reflectance of 40% to 80% for visible light from 400 nm to 750 nm when incident perpendicularly to the surface. If the average reflectance in this band is less than 40%, the sheet will not have a metallic luster appearance, and if the average reflectance in this band is more than 80%, a sufficient amount of light will not transmit when illuminated from a light source such as an LED from behind, making the sheet unsuitable for applications requiring light transmission.

[0012] The average reflectance of visible light from 400 nm to 750 nm when incident perpendicularly on the surface can be calculated by using the absolute reflectance data for every 1 nm of wavelength within that band measured by a spectrophotometer, calculating the area enclosed by the reflection curve and the wavelength band based on Simpson's formula, and dividing the area by 350 nm, which is the width of the wavelength band. The method for measuring the average reflectance will be described in detail later.

[0013] In addition, in order to suppress color variation when viewed obliquely, the sheet of the present invention has a color value calculated by a formula specified in JIS Z 8781 (2013) using the spectral reflectance measured at an incidence angle of X° relative to the vertical direction of the sheet surface. * [X°], b * When [X°] is set, a 50 cm square sheet is divided into 25 equal 10 cm squares, and the 25 points at the center of each square are measured and calculated. * [60°] and b * For [60°], a * Difference between maximum and minimum values ​​of [60°] Δa * [60°], and b * Difference between maximum and minimum values ​​of [60°] Δb * [60°] respectively satisfy the following formulas (i) and (ii). * [60°] is Δa * [60°]≦4.5 is preferable, and Δa * It is more preferable that [60°]≦4.3 is satisfied. From the same viewpoint, Δb * [60°] is Δb * [60°]≦3.5 is preferable, and Δb * It is more preferable that [60°]≦3.0. Formula (i) Δa * [60°]≦5.0 Formula (ii)Δb * [60°]≦4.0.

[0014] From a similar perspective, * Difference between maximum and minimum values ​​of [30°] Δa * [30°], and b *Difference between maximum and minimum values ​​of [30°] Δb * [30°] preferably satisfies the following formulas (iii) and (iv). * [30°] is Δa * [30°]≦4.0 is preferable, and Δa * It is more preferable that [30°]≦3.7 is satisfied. * [30°] is Δb * [30°]≦3.5 is preferable, and Δb * It is more preferable that [30°]≦3.0. Formula (iii) Δa * [30°]≦4.5 Formula (iv)Δb * [30°]≦4.0.

[0015] a * [X°], b * [X°] can be calculated from the average spectral reflectance curve for each angle obtained by measurement with a spectrophotometer using the formula specified in JIS Z 8781 (2013). Details of the measurement method will be described later.

[0016] In order to obtain a sheet that satisfies formulas (i) and (ii) or all of formulas (i) to (iv) while having an average reflectance of 400 nm to 750 nm visible light when incident perpendicularly to the sheet surface of 40% or more and 80% or less, a method of laminating multiple films can be used, the details of which will be described later.

[0017] The sheet of the present invention is preferably formed by laminating two or more films in order to satisfy the above-mentioned preferred range of visible light reflectance and all of formulas (i) and (ii) or formulas (i) to (iv).

[0018] When laminating films, it is preferable to select and laminate the films according to the following procedure. First, for each film, the reflection spectrum in the wavelength range of 400 nm to 1200 nm is measured at 10 cm intervals in the width direction, and the correlation coefficient of the reflection spectrum measured previously is calculated for each overlapping position when laminated. Here, the width direction refers to the direction perpendicular to the film plane to the direction in which the film runs during the manufacturing process (the winding direction in the case of a film roll). Films whose maximum value of the obtained correlation coefficient is greater than 0.75 and less than 0.98, and whose minimum value is greater than 0.75 and less than 0.98, are laminated together to obtain a sheet.

[0019] Conventional metallic luster laminate films reflect light in a wide wavelength band from visible light to near infrared light, which means that the reflectance in the reflection spectrum is prone to variation. In addition, when viewed obliquely, the reflection band of conventional metallic luster laminate films shifts depending on the viewing angle, which means that the variation in the reflectance of the spectrum enters the visible light band, resulting in variation in color tone.

[0020] On the other hand, by laminating films having a maximum value of the correlation coefficient greater than 0.75 and less than 0.98 and a minimum value of 0.75 or more and less than 0.98 as described above, the variation in the reflectance of the waveform of the reflection spectrum in the sheet is averaged, and the reflectance of each wavelength band approaches flat. As a result, even if the reflection band shifts when viewed from an oblique angle, the reflectance is stable in the entire visible light band, and the color tone variation is suppressed, making it easy to satisfy all of the formulas (i) and (ii) or (i) to (iv) in a size of 50 cm square. From the above viewpoint, the maximum value of the correlation coefficient is preferably 0.90 or more and 0.98 or less, and the minimum value of the correlation coefficient is preferably 0.75 or more and less than 0.90.

[0021] When the maximum correlation coefficient of the reflectance spectrum of the films to be laminated is 0.98 or less, films having the same reflectance spectrum are not laminated together, and the variation in the reflectance of each film is not emphasized. Therefore, the color variation is suppressed, and it is easy to satisfy all of the formulas (i) and (ii) or (i) to (iv) in a size of 50 cm square. On the other hand, when the minimum correlation coefficient is 0.75 or more, the reflectance spectrum of each film does not differ excessively, and when the laminated sheet is formed, the variation in the reflectance of each film (especially the variation in the width direction) is unlikely to remain. Therefore, the color variation when viewed from an oblique angle is suppressed, and it is easy to satisfy all of the formulas (i) and (ii) or (i) to (iv) in a size of 50 cm square.

[0022] It is preferable that the sheet of the present invention does not undergo delamination in an adhesion test by the cross-cut method according to JIS K 5600 (1999). Hereinafter, the cross-cut method according to JIS K 5600 (1999) may be simply referred to as the cross-cut method (details of the measurement method will be described later). If delamination does not occur by the cross-cut method, delamination due to stress during cutting in the processing step of the sheet is suppressed, and the processing yield is improved.

[0023] One method for satisfying this requirement is to form a laminate structure in which the total number of A layers and B layers of the film described below is 499 or more, and to make the basic skeleton of the thermoplastic resin that is the main component of both layers the same. Here, the basic skeleton of a thermoplastic resin refers to the structural unit that is most abundant in the molecular chain of the thermoplastic resin. For example, if the thermoplastic resin is polyethylene terephthalate, the ethylene terephthalate unit corresponds to the basic skeleton.

[0024] In order to satisfy the above-mentioned condition of the correlation coefficient between films, it is preferable to use a film having a large area and more uniform optical properties as the film constituting the sheet of the present invention. As a method for obtaining such a film, for example, a method such as that described in Patent Document 3 can be mentioned, but it is not limited to such a method. Hereinafter, the film constituting the sheet of the present invention will be described.

[0025] In the case where the sheet of the present invention is formed by laminating two or more films, at least two of the films have a layer (A layer) mainly composed of thermoplastic resin A and a layer (B layer) mainly composed of thermoplastic resin B other than thermoplastic resin A, and the A layer and the B layer are alternately positioned in the thickness direction, the total number of A layers and B layers is 499 or more, and the film has three or more thick film layers having a thickness of 1 μm or more and 20 μm or less, and the thick film layers are the outermost layers on both sides. Here, the main component refers to a component that is contained in an amount of more than 50 mass% and 100 mass% or less when the total components constituting the layer are taken as 100 mass%. Here, the main component refers to a component that is contained in an amount of more than 50 mass% and 100 mass% or less when the total components constituting the layer are taken as 100 mass%, and can be interpreted in the same manner hereinafter.

[0026] In addition, the requirement that "having a layer (layer A) whose main component is thermoplastic resin A and a layer (layer B) whose main component is thermoplastic resin B other than thermoplastic resin A" means that one film has this configuration, and it does not matter whether the thermoplastic resins A and B, or the thermoplastic resins A and B, are the same or different between one film and another film.

[0027] From the viewpoint of uniformly reflecting visible light, the film constituting the sheet of the present invention has layers A and B, the layers A and B being alternately positioned in the thickness direction, and the total number of layers A and B is preferably 499 or more. From the above viewpoint, the total number of layers A and B is more preferably 601 or more, even more preferably 701 or more, and particularly preferably 801 or more. By having a total number of layers A and B of 499 or more, the film can reflect visible light more uniformly, and the variation in the reflection spectrum is reduced, making it easier to satisfy the above-mentioned condition for the correlation coefficient between the films. As a result, the Δa of the sheet * [60°], Δb * [60°], Δa * [30°], Δb * [30°] becomes easier to control within the preferred range.

[0028] From the viewpoint of appearance and handling, the film constituting the sheet of the present invention preferably has three or more thick film layers each having a thickness of 1 μm or more and 20 μm or less, and the thick film layer is the outermost layer on both sides. Since the thick film layer is a layer having a larger thickness than the other layers constituting the film, the thickness of the layers other than the thick film layer constituting the film is at the nm level. From the above viewpoint, the thickness of the thick film layer is more preferably 5 μm or more and 10 μm or less. When the thickness of the thick film layer is 1 μm or more, the occurrence of flow marks due to lamination defects is suppressed, and appearance defects due to streaks caused by surface unevenness are less likely to occur. In addition, since the lamination accuracy is improved, the variation in the reflection spectrum caused by lamination defects is also reduced, making it easier to satisfy the above-mentioned condition of the correlation coefficient between films. On the other hand, when the thickness of the thick film layer is 20 μm or less, the necessary reflection characteristics can be achieved without excessively increasing the overall thickness, so that the stiffness is not excessively strong and the handling properties are good, and it can be suitably used for mirror displays and decorative applications.

[0029] Examples of methods for forming such a thick film layer include a method for adjusting the layer structure of the feed block used for lamination and the slit thickness. The thickness of the thick film layer can be measured by observing a cross section in the thickness direction (a cross section parallel to the thickness direction, in other words, a cross section perpendicular to the film surface) using a transmission electron microscope, and the details of the measurement method will be described later.

[0030] An example of a preferred layer structure of the film constituting the sheet of the present invention will be described with reference to the drawings. FIG. 1 is a diagram in which the thickness of the A layer and the B layer are plotted against the layer number in a film in which the A layer and the B layer are alternately laminated in the thickness direction. The layer thickness corresponds only to the integer layer numbers in FIG. 1, with the A layer corresponding to the odd number and the B layer corresponding to the even number. Also, the reference numbers 1 to 5 in FIG. 1 respectively mean the layer number, layer thickness, thickness of the thick film layer, thickness of the A layer, and thickness of the B layer. The layer numbers can be assigned in order starting from any surface.

[0031] When the layer with relatively high crystallinity is the A layer, it is preferable that the thick layer of the film is formed of the A layer from the viewpoint of improving the impression resistance. In the case of a layer structure in which the layer thickness increases and then decreases from one surface to the opposite surface as shown in FIG. 1, even if a lamination defect occurs in a very small part and deviates from the design value, since there are layer pairs of layers with the same layer thickness in other parts, the variation in the reflection spectrum is suppressed. In addition, since lamination defects are likely to occur at the point where the layer structure changes from decrease to increase or from increase to decrease, which causes the variation in the reflection spectrum, it is preferable to provide a thick layer with a thickness of 1 μm or more and 20 μm or less at the point indicated by the symbol 3. When a thick layer is provided, lamination defects are reduced, so that the reflection of light is less likely to shift from the design value, and the variation in the reflection spectrum of the film is suppressed.

[0032] For the sake of convenience, the layer thickness configuration in Fig. 1 will be referred to as a four-step gradient structure in the present invention. Here, the "four-step gradient structure" refers to a structure in which the layer thickness can be approximated by four monotonically increasing and / or decreasing curves.

[0033] In the film constituting the sheet of the present invention, the thick film layer formed by the A layer is preferably located at the outermost layer on both sides of the film and at the change point of the monotonically increasing curve and / or monotonically decreasing curve, i.e., the intermediate layer. In addition, if the thick film layer has a gradient of two or more steps including three or more layers, even if a lamination defect occurs in a very small part and the designed layer thickness is deviated from, layers of the same thickness exist in other parts, so that the variation in the reflection spectrum of the film can be suppressed.

[0034] In order to suppress the variation in the reflection spectrum, the number of layers having a layer-to-layer thickness of 10 nm or more and less than 220 nm is preferably greater than the number of layers having a layer-to-layer thickness of 220 nm or more and 350 nm or less. Here, the "layer-to-layer thickness" in the present invention refers to the sum of the layer thicknesses of adjacent A and B layers. In addition, the layer-to-layer thickness must be the sum of the layer thickness of the m-th A layer counted from one film surface for only the A layer, and the layer thickness of the m-th B layer counted from the same surface for only the adjacent B layer. Here, m represents an integer. For example, when the layers are arranged in the order of A1 layer / B1 layer / A2 layer / B2 layer / A3 layer / B3 layer... from one film surface to the opposite surface, the A1 layer and the B1 layer are the first layer pair, the A2 layer and the B2 layer are the second layer pair, and the A3 layer and the B3 layer are the third layer pair.

[0035] When the number of layer pairs having a layer-pair thickness of 10 nm or more and less than 220 nm is greater than the number of layer pairs having a layer-pair thickness of 220 nm or more and 350 nm or less, the decrease in reflectance on the low wavelength side in the reflection band of the wavelength band 400 nm to 1100 nm is suppressed, so that the redness of the film can be reduced. This is because the density of the layer pairs causing reflection on the low wavelength side is maintained. Therefore, as the layer-pair thickness sequence of the layers constituting the film, it is preferable that the layer-pair thickness does not increase or decrease monotonically in an arithmetic progression, but increases or decreases in a geometric progression while satisfying the above conditions. More preferably, the layer pairs having a layer-pair thickness of 120 nm or more and less than 220 nm are 1.05 times or more and 2.50 times or less than the layer pairs having a layer-pair thickness of 220 nm or more and 350 nm or less. When a film contains a thick layer, the layer pair is counted including the thick layer. However, since a layer pair including a thick layer has a thickness exceeding 350 nm, it does not fall into either a layer pair with a layer-pair thickness of 10 nm or more and less than 220 nm, or a layer pair with a layer-pair thickness of 220 nm or more and 350 nm or less.

[0036] Thermoplastic resin A and thermoplastic resin B in the film constituting the sheet of the present invention may be homopolymers or copolymers. Furthermore, layer A and layer B may be composed of only thermoplastic resin A or thermoplastic resin B, or may be a mixture of two or more types of resins. Among these, thermoplastic resins A and B are preferably polyester resins from the viewpoints of strength, heat resistance, transparency, and versatility.

[0037] The polyester resin is preferably a polyester obtained by polymerization of a monomer mainly composed of an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid and a diol. Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Examples of the aliphatic dicarboxylic acid include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof. Among them, terephthalic acid and 2,6-naphthalenedicarboxylic acid, which have a high refractive index, are preferred. These acid components may be used alone or in combination of two or more, and may be partially copolymerized with oxyacids such as hydroxybenzoic acid.

[0038] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-hexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol. Among these, ethylene glycol is preferably used. These diol components may be used alone or in combination of two or more.

[0039] As the thermoplastic resins A and B, from the viewpoints of strength and versatility, it is preferable to use, among the above-mentioned polyesters, polyethylene terephthalate and its copolymers, polyethylene naphthalate and its copolymers, polybutylene terephthalate and its copolymers, polybutylene naphthalate and its copolymers, polyhexamethylene terephthalate and its copolymers, polyhexamethylene naphthalate and its copolymers, etc.

[0040] A preferred combination of thermoplastic resins A and B is one in which both thermoplastic resins have the same basic skeleton. Here, the basic skeleton refers to the structural unit that is most abundant in all structural units constituting the thermoplastic resin. For example, if the thermoplastic resin is polyethylene terephthalate, the basic skeleton is an ethylene terephthalate skeleton. As such a combination of thermoplastic resins A and B, for example, one thermoplastic resin is polyethylene terephthalate, and the other thermoplastic resin is a polymer (copolymer) consisting of ethylene terephthalate units and cyclohexane 1,4-dimethylene terephthalate units, with a relatively large amount of ethylene terephthalate units. When thermoplastic resins with the same basic skeleton are used, problems such as lamination defects such as flow marks and peeling between layers are less likely to occur during film formation.

[0041] From the viewpoints of resistance to pressure marks (dent resistance) and stiffness of the film itself, it is preferable to use polyethylene terephthalate or polyethylene naphthalate as the thermoplastic resin A. From the viewpoint of suppressing an increase in the refractive index, it is preferable to use, as the thermoplastic resin B, a copolymer having the same basic skeleton as the thermoplastic resin A, containing isophthalic acid, naphthalenedicarboxylic acid, diphenyl acid, or cyclohexanedicarboxylic acid as a constituent unit, or containing spiroglycol, cyclohexanedimethanol, bisphenoxyethanolfluorene, or bisphenol A component, mixed with the thermoplastic resin A or used alone.

[0042] In the sheet of the present invention, it is preferable that the A layer and the B layer contain a crystalline resin, and more preferably, the proportion of the crystalline resin in the total components constituting the A layer is more than 15% by mass and 100% by mass or less, and the proportion of the crystalline resin in the total components constituting the B layer is 15% by mass or more and 75% by mass or less. Here, the crystalline resin refers to a thermoplastic resin in which a peak of the crystalline melting point is observed in the DSC curve when the resin is heated from 30°C to 300°C at a heating rate of 10°C per minute using a differential scanning calorimeter (DSC). By containing a certain proportion or more of the crystalline resin in both the A layer and the B layer, the rigidity of each layer is improved, and the laminated structure of the sheet is less likely to deform even under high temperature and high pressure environments. Therefore, when a laminate obtained by laminating a layer mainly composed of a polycarbonate resin to such a sheet is used for injection molding, deformation of the laminated structure of the sheet part due to injection of the molten resin at high temperature and high pressure and defects caused by the deformation are less likely to occur. On the other hand, from the viewpoint of suppressing an increase in the refractive index of the B layer, the ratio of the crystalline resin to all the components constituting the B layer is preferably 75% by mass or less, more preferably 50% by mass or less, and even more preferably 20% by mass or less. From the viewpoint of film formability, the ratio of the crystalline resin to all the components constituting the A layer is preferably 80% by mass or more, and preferably 90% by mass or more. In consideration of the above viewpoint and film formability, it is preferable that the A layer is the outermost layer, and the ratio of the crystalline resin to all the components constituting the A layer is higher than the ratio of the crystalline resin to all the components constituting the B layer.

[0043] Next, a method of laminating a plurality of films to form a sheet will be described. For example, one film roll is cut in half parallel to the longitudinal direction and wound up, and the resulting two film rolls are unwound, and the films are laminated so that the top left side of one film roll overlaps the top left side of the other film roll, thereby satisfying the above-mentioned condition of the correlation coefficient between the films over the entire width of the laminate, and easily satisfying all of formulas (i) and (ii), or formulas (i) to (iv), in a laminated sheet of 50 cm square.

[0044] The film constituting the sheet of the present invention preferably has an easy-adhesion layer on at least one surface. The easy-adhesion layer refers to a layer for enhancing adhesion to other members such as films (different from the adhesive layer described below). The method for forming the easy-adhesion layer is not particularly limited, but a coating method is preferred in that a thin film layer can be formed uniformly. The coating method may be a so-called offline coating method in which a coated film is obtained by unwinding, coating, and drying a film in a separate process from the film production process, or a so-called in-line coating method in which a thermoplastic resin is extruded by an extruder, the thermoplastic resin is formed into a sheet-like film, and coating is performed during the film production process to obtain a coated film in one go.

[0045] The adhesive layer may contain known polyester, acrylic, urethane, epoxy, and other resins, either alone or in combination, to provide various functions such as holding lubricant particles and sealing oligomers precipitated from the film. It may also contain a melamine, oxazoline, or carbodiimide crosslinking agent.

[0046] Furthermore, if the adhesive layer is made of only one component, it is likely to become charged, and as a result, static electricity may cause foreign matter to be mixed into the adhesive layer described later, resulting in a problem of defective appearance. Therefore, it is preferable that the adhesive layer contains a conductive polymer from the viewpoint of preventing static electricity. Examples of conductive polymers include polypyrrole, polyaniline, polyacetylene, polythiophene vinylene, polyphenylene sulfide, poly-p-phenylene, polyheterocycle vinylene, etc., and (3,4-ethylenedioxythiophene) (PEDOT) is particularly preferable. These components may be used alone or in combination.

[0047] The sheet of the present invention preferably has a structure in which films having little variation in the reflection spectrum in the width direction obtained by the method described above are laminated together via an adhesive layer so as to meet the correlation coefficient condition as described above.

[0048] In addition, the sheet of the present invention may be laminated on one or both sides with a layer mainly composed of polycarbonate resin via an adhesive layer in order to improve moldability, etc. In other words, the laminate of the present invention is a laminate obtained by laminating a layer mainly composed of polycarbonate resin to a sheet. Note that when a layer contains multiple polycarbonate resins, if the total amount of all the polycarbonate resins in the layer exceeds 50 mass % in the layer, the layer is considered to be mainly composed of polycarbonate resin.

[0049] The polycarbonate resin used in the present invention is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include polycarbonate resins obtained by using 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), flame-retardant polycarbonate resins obtained by using a mixture of bisphenol A and 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane (tetrabromobisphenol A), and bisphenol A-based polycarbonate-polyorganosiloxane copolymers. The above polycarbonate resins may contain an ultraviolet absorber added thereto for the purpose of imparting weather resistance.

[0050] The thickness of the layer mainly composed of polycarbonate resin in the laminate of the present invention is preferably 50 μm or more and 500 μm or less from the viewpoint of the molding processability of the laminate sheet. When the thickness of the layer mainly composed of polycarbonate resin is 50 μm or more, the moldability during molding processing is improved. On the other hand, when the thickness of the layer is 500 μm or less, the processability and workability as a molding film can be ensured, and at the same time, the increase in manufacturing costs can be reduced. From the above viewpoint, the preferred range of the thickness of the layer mainly composed of polycarbonate resin is 80 μm or more and 400 μm or less, more preferably 100 μm or more and 300 μm or less, and even more preferably 120 μm or more and 250 μm or less.

[0051] The method of laminating films together via an adhesive layer or laminating a layer mainly composed of polycarbonate resin to a sheet is not particularly limited, but dry lamination is preferably used. The adhesive used in the adhesive layer of the present invention is not particularly limited as long as it does not impair the effects of the present invention, but a two-component curing polyurethane adhesive is preferably used from the viewpoint of heat resistance during molding, and a two-component curing modified olefin adhesive is used from the viewpoint of durability. The two-component curing polyurethane adhesive contains a base agent (polyol) having a hydroxyl group at the polymer end and a curing agent (polyisocyanate) having an isocyanate group, and is cured by forming a urethane bond through the reaction of the hydroxyl group and the isocyanate group.

[0052] As the polyol, polyether polyol or polyester polyol can be used. For example, as the polyether polyol, polyoxyethylene polyol, polyoxypropylene polyol, polyoxyethylene-propylene copolymer polyol, polytetramethylene polyol, etc. can be used alone or in mixtures. As the polyester polyol, polyols obtained by polycondensation of dicarboxylic acid (adipic acid, succinic acid, maleic acid, phthalic acid, etc.) and glycol (ethylene glycol, propylene glycol, 1,4-butylene glycol, 1,6-hexane glycol, neopentyl glycol, etc.) can be used.

[0053] Examples of the polyisocyanate include 2,4-tolylene diisocyanate, xylylene diisocyanate, 2,6-tolylene diisocyanate, 4,4-diphenylmethane diisocyanate, polymethylene polyphenylene polyisocyanate, carbodiimide-modified MDI, aromatic polyisocyanates such as naphthalene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and alicyclic polyisocyanates.

[0054] The modified olefin resin used in the two-component curing modified olefin adhesive is preferably an olefin resin modified with an unsaturated carboxylic acid and / or an acid anhydride, or an acidic vinyl compound. The olefin resin to be modified is preferably an olefin resin having 2 to 8 carbon atoms, and preferred examples include ethylene, propylene, butylene, heptene, and octene. The unsaturated carboxylic acid and its acid anhydride used for modification include, for example, maleic acid, fumaric acid, itaconic acid, citraconic acid, allylsuccinic acid, mesaconic acid, aconitic acid, and their acid anhydrides, and the acidic vinyl compound includes, for example, acrylic acid, methacrylic acid, and the like.

[0055] In addition, the adhesive layer used in the present invention may contain various additives, such as viscosity modifiers, leveling agents, antigelling agents, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, etc. The thickness of the adhesive layer of the present invention is preferably 0.5 μm or more and 30 μm or less from the viewpoint of achieving both adhesiveness and film appearance. The adhesive layer here refers to a layer that bonds the films forming the sheet together, or the sheet and a layer mainly composed of polycarbonate resin.

[0056] Next, an example of a preferred method for producing the sheet of the present invention will be described below, but the sheet of the present invention is not limited to the following example.

[0057] First, the film manufacturing method will be described. Thermoplastic resin A and thermoplastic resin B are prepared in the form of pellets. The pellets are dried in hot air or under vacuum as necessary, and then fed to two extruders, respectively. In each extruder, each thermoplastic resin is heated and melted at a temperature above its melting point, and the extrusion amount is uniformized and extruded using a gear pump or the like, and then foreign matter and denatured resins are removed from each extruded thermoplastic resin through a filter or the like.

[0058] Next, the thermoplastic resin A and the thermoplastic resin B sent out from different flow paths using two extruders are sent to a multi-layer lamination device. As the multi-layer lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but in particular, in order to efficiently obtain the film constituting the sheet of the present invention, it is desirable to use a feed block containing at least two or more separate members having a large number of fine slits. When such a feed block is used, the device does not become extremely large, so there is little foreign matter due to thermal deterioration, and even if the number of layers is extremely large, lamination can be performed with high precision. In addition, the lamination precision in the width direction is significantly improved compared to the conventional technology, and it is also easy to form an arbitrary layer thickness configuration. In this device, the thickness of each layer can be adjusted by the slit shape (length, width, gap), so it is possible to achieve an arbitrary layer thickness, and the layer configuration required for the film constituting the sheet of the present invention can be easily achieved.

[0059] When the layer thickness distribution has a gradient structure of two or more steps, the change in layer thickness from a thin layer to a thick layer or from a thick layer to a thin layer becomes very steep. As described above, a feed block containing at least two or more separate members having a large number of fine slits is preferably used to manufacture the film constituting the sheet of the present invention. However, at the point where the thermoplastic resins fed from the separate feed blocks join, the layer thickness distribution changes immediately after joining, which is a major factor in causing color variation in the width direction. Furthermore, the resin speed near the pipe is reduced due to the influence of the wall surface of the pipe on the path from the feed block to the die, and the color uniformity in the width direction of the film is further deteriorated due to the difference in flow speed between the wall surface of the pipe and the center of the pipe.

[0060] Therefore, by replacing a certain distance of the resin joining part of the film's outermost layer and the separate feed block with the same polymer to provide a thick film layer, a film that expresses a uniform color tone in the width direction can be obtained without destroying the lamination ratio. In this case, if the outermost layers on both sides of the film are made of thermoplastic resin A, the layer (A layer) made of thermoplastic resin A becomes the thick film layer. In addition, the resin for the middle thick film layer is preferably a thermoplastic resin with relatively high crystallinity to improve the resistance to pressure marks, and is usually the same layer as the outermost layer. The thickness of the thick film layer is preferably adjusted by adjusting each flow rate corresponding to the thickness of the corresponding layer with the gap of the slit, and in this case, the gap accuracy of each slit gap is preferably ±10 μm or less. By using such a special feed block, a film with high accuracy and a gradient structure of two or more stages can be obtained.

[0061] Next, the layer thickness of each layer of the present invention must be designed based on the following formula (v): The film constituting the sheet of the present invention is capable of reflecting / transmitting light, and the reflectance can be controlled by the refractive index difference between the layer made of thermoplastic resin A (layer A) and the layer made of thermoplastic resin B (layer B) and the number of layers. Formula (v): 2×(na·da+nb·db)=λ na: Average in-plane refractive index of A layer nb: Average in-plane refractive index of B layer da: A layer thickness (nm) db: Layer thickness of B layer (nm) λ: Main reflection wavelength (first reflection wavelength) The molten laminate thus formed into the desired layer structure is then molded into a desired shape by a die and discharged. The multi-layer laminated sheet discharged from the die is then extruded onto a rotating cooling body such as a casting drum, and cooled and solidified to obtain a cast film (unstretched film). In this case, it is preferable to use a wire-shaped, tape-shaped, wire-shaped, or knife-shaped electrode to adhere to a rotating cooling body such as a casting drum by electrostatic force and rapidly solidify. In addition, a method of rapidly solidifying by blowing air from a slit-shaped, spot-shaped, or planar device to adhere to a rotating cooling body such as a casting drum or by adhering to a rotating cooling body with a nip roll is also preferable.

[0062] The thus obtained casting film (unstretched film) is preferably biaxially stretched as necessary. Biaxial stretching refers to stretching in the longitudinal direction and the width direction. Stretching may be performed in two axial directions sequentially, or in two directions simultaneously. Furthermore, the film may be re-stretched in the longitudinal direction and / or the width direction. The longitudinal direction refers to the running direction of the film (the winding direction in the case of a film roll), and the width direction refers to the direction perpendicular to the longitudinal direction within the film plane.

[0063] First, the case of sequential biaxial stretching will be described. In the case of sequential biaxial stretching, first, longitudinal stretching is performed to obtain a uniaxially stretched film. The longitudinal stretching here refers to stretching for giving molecular orientation to the film in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage or in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of thermoplastic resin, but is usually preferably 2 to 15 times, and when polyethylene terephthalate is used as either thermoplastic resin A or B, 2 to 7 times is particularly preferably used. In addition, the stretching temperature is preferably the glass transition temperature of the higher of the thermoplastic resins A and B that constitute the film to the glass transition temperature + 100°C, and when polyethylene terephthalate is used as either thermoplastic resin A or B, 75°C to 175°C is preferable.

[0064] When providing an easy-adhesion layer on a film, a method of coating and laminating with a coating agent containing the above-mentioned components is preferred. Methods of coating with a coating agent include a method of coating in a separate process from the film manufacturing process, that is, a so-called offline coating method, and a method of laminating an easy-adhesion layer at once by coating during the film manufacturing process, that is, a so-called in-line coating method. From the viewpoints of cost and uniformity of coating thickness, it is preferable to adopt the in-line coating method, and the solvent of the coating liquid used in this case is preferably aqueous from the viewpoints of environmental pollution and explosion resistance, and the most preferred embodiment is to use water.

[0065] When laminating the easy-adhesion layer by in-line coating, the coating agent constituting the easy-adhesion layer is continuously applied to the uniaxially stretched film. For example, the coating agent (water-based coating agent) using water as a solvent can be applied by reverse coating, spray coating, bar coating, gravure coating, rod coating, and die coating. The easy-adhesion layer may contain a crosslinking agent, an antioxidant, a heat stabilizer, a weather stabilizer, an ultraviolet absorber, an organic slippery material, a pigment, a dye, organic or inorganic particles, a filler, a surfactant, etc., as long as the effect of the invention is not impaired.

[0066] The subsequent stretching in the width direction refers to stretching to give molecular orientation in the width direction of the film, and is usually performed by using a tenter to convey the uniaxially stretched film while holding both ends in the width direction with clips, preheating the film by applying heat, and then stretching it in the width direction. The water-based coating agent applied just before the tenter is dried during this preheating. The stretching ratio varies depending on the type of thermoplastic resin, but is usually preferably 2 to 15 times, and when polyethylene terephthalate is used as either thermoplastic resin A or B, it is particularly preferably 2 to 7 times. In addition, the stretching temperature is preferably the glass transition temperature of the higher of the thermoplastic resins A and B that constitute the film to the glass transition temperature + 120°C, and when polyethylene terephthalate is used as either thermoplastic resin A or B, it is preferably 75°C to 195°C.

[0067] The biaxially stretched film is preferably heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. After the biaxially stretched film is heat-treated, it is uniformly cooled slowly to room temperature and wound up by a winder. If necessary, a relaxation treatment or the like may be performed in combination during the heat treatment and the slow cooling.

[0068] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the coating agent that forms the easy-adhesion layer is continuously applied to the obtained cast film. As the coating method of the coating agent (water-based coating agent) that uses water as a solvent, for example, reverse coating method, spray coating method, bar coating method, gravure coating method, rod coating method and die coating method can be used.

[0069] Next, the cast film (unstretched film) coated with the coating agent is introduced into a simultaneous biaxial tenter, and the film is conveyed while both ends are held by clips, and stretched simultaneously and / or stepwise in the longitudinal and transverse directions. The simultaneous biaxial stretching machine may be of the pantograph type, screw type, drive motor type, or linear motor type, but the drive motor type or linear motor type is preferred, since it can change the stretching ratio at any desired position and can perform relaxation treatment at any desired location. The stretching ratio varies depending on the type of thermoplastic resin, but usually, an area ratio of 6 to 50 times is preferred, and an area ratio of 8 to 30 times is particularly preferred. In particular, in the case of simultaneous biaxial stretching, in order to suppress the in-plane orientation difference, it is preferred that the stretching ratios in the longitudinal and transverse directions are the same and that the stretching speeds are approximately the same. In addition, the stretching temperature is preferably the glass transition temperature of the higher of the thermoplastic resins A and B constituting the film to the glass transition temperature + 120°C, and when polyethylene terephthalate is used as either the thermoplastic resin A or B, it is preferably 75°C to 195°C.

[0070] The biaxially stretched film is preferably subsequently subjected to heat treatment in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. During this heat treatment, it is also preferable to instantly perform a relaxation treatment in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone in order to suppress the distribution of the main orientation axis in the width direction. After the heat treatment is performed on the biaxially stretched film in this way, it is uniformly cooled slowly to room temperature and wound up by a winder. If necessary, a relaxation treatment may be performed in the longitudinal direction and / or width direction during the heat treatment and slow cooling, and it is also preferable to instantly perform a relaxation treatment in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone.

[0071] The sheet of the present invention can be obtained by subsequently heat laminating the film obtained by the above-mentioned method or laminating it via an adhesive layer. In addition, the obtained sheet may be laminated on one or both sides with a layer mainly composed of a polycarbonate resin for the purpose of improving moldability, etc., to obtain a laminate.

[0072] In obtaining a composition used to obtain a layer mainly composed of a polycarbonate resin, that is, a composition mainly composed of a polycarbonate resin, it is preferable to use a melt-kneading method in which the composition is produced by melt-kneading each component including the polycarbonate resin. There is no particular restriction on the device used in the melt-kneading method, and known mixers such as a kneader, a roll mill, a Banbury mixer, and a single-screw or twin-screw extruder can be used. Among these, from the viewpoint of productivity, it is preferable to use a single-screw extruder.

[0073] Next, the molten polycarbonate resin composition obtained by the above-mentioned method is extruded from a T-die into a sheet shape, and cooled and solidified on a temperature-controlled cast roll to obtain a polycarbonate resin film (unstretched film). The temperature of the cast roll is preferably controlled to 10°C or higher and 60°C or lower. In addition, in the stage of cooling and solidifying the sheet-like material on the cast roll, it is also preferable to nip it with a rubber shaping roll whose temperature is controlled to 20°C or higher and 50°C or lower. As the layer mainly composed of polycarbonate resin to be laminated on the sheet of the present invention, the unstretched film may be used, or when the main component is a stretchable polycarbonate resin, a stretched film obtained by uniaxial or biaxial stretching treatment by a conventionally known method may be used.

[0074] The method of laminating such a film mainly composed of polycarbonate resin to the sheet of the present invention to form a laminate is not particularly limited, but it is preferable to use dry lamination. The adhesive used in the adhesive layer at this time is not particularly limited as long as it does not impair the effects of the present invention, but a two-component curing polyurethane adhesive is preferable from the viewpoint of heat resistance during molding, and a two-component curing modified olefin adhesive is preferable from the viewpoint of durability. At this time, the coating amount of the adhesive is 1 to 10 g / m2 in wet coating amount. 2 The drying conditions are preferably a temperature of 70 to 90° C. and a speed of 15 to 30 m / min. In addition, in lamination, nipping with nip rolls is also preferable, and the nip pressure and temperature are preferably 0.3 to 0.5 MPa and 30 to 50° C., respectively. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various properties were measured by the following methods, and the raw materials used in the production of the laminated sheet were as follows.

[0076] [Evaluation method of various characteristics] (1) Film layer structure, layer thickness, and total thickness A film sample was obtained by cutting out a cross section perpendicular to the film surface using a microtome. Next, a transmission electron microscope (TEM) (Hitachi, Ltd., H-7100FA type) was used to observe the cross section of the film at 40,000 times magnification at an acceleration voltage of 75 kV, and the cross section was photographed to confirm the layer structure, and the layer thickness was measured using the length measurement function of the transmission electron microscope. The total thickness of each layer was taken as the total film thickness. In addition, the sample was stained using RuO4 to obtain high contrast during observation.

[0077] A specific method for confirming and determining the layer structure and layer thickness of the film will be described. The cross-sectional image obtained in the TEM observation was converted into a compressed image file (JPEG format), and position-brightness data was obtained by line profile along the thickness direction of the film using ImagePro-10 (sold by Hakuto Co., Ltd.). Then, a five-point moving average process was performed on the profile obtained by plotting the relationship between position and brightness using a spreadsheet software (Microsoft Corporation "Excel" (registered trademark) 2016). This process was performed by performing brightness averaging process on five consecutive measurement positions, and the same calculation was performed by changing the position one point at a time and continuously processing, and an averaged position-brightness profile was obtained. In the obtained averaged position-brightness profile, the position surrounded by the inflection points where the slope changes from positive to negative or from negative to positive was determined to be one layer. For each layer obtained by this method, position-brightness data was then obtained in the planar direction of the film (direction perpendicular to the thickness direction). After calculating the average value and standard deviation of the brightness obtained for each layer, if the difference between the average values ​​of the brightness of two adjacent layers was greater than any of the standard deviations of the brightness of the adjacent thermoplastic resin layers, the two adjacent layers were determined to be different. In addition, the difference (distance) in the positions between the inflection points was calculated as the layer thickness of each layer. The average value of the sum of the layer thicknesses of the adjacent A and B layers from one film surface to the opposite surface was calculated for all pairs in sequence. A group in which the difference between the average layer thickness of the pair of adjacent A and B layers and the average layer thickness of the adjacent pair is continuously monotonically increasing or monotonically decreasing within a range of 50 nm or less was defined as a gradient structure. A gradient structure is one that has a positive or negative gradient such that the square of R is 0.5 or more when the relationship between the pair number and the average layer thickness is approximated by least squares. For example, the configuration of Figure 1 was called a four-step gradient structure. However, the average thickness of the pair including the thick film layer was excluded from the least squares approximation.

[0078] (2) Maximum and minimum values ​​of correlation coefficient of reflectance spectrum From a roll (width direction length 1100 mm) of one film (film 1) constituting the sheet, 11 samples of 10 cm square were cut out at intervals of 10 cm in the width direction, and black tape was attached to the back of the measurement surface. Next, the relative reflectance of each sample at an incident angle of 10° was measured using a spectrophotometer (Hitachi, Ltd., U-4100 Spectrophotometer). The inner wall of the integrating sphere attached to the spectrophotometer used was barium sulfate, and the standard plate was aluminum oxide. The measurement conditions were a wavelength band of 400 nm to 1200 nm, a slit of 2 nm (visible) / automatic control (infrared), a gain of 2, and a scanning speed of 600 nm / min. Under the above conditions, the reflection spectrum of each sample from 400 nm to 1200 nm was obtained. For the other film (film 2), samples (hereinafter sometimes referred to as the corresponding samples) were similarly cut out from the roll at positions that overlapped the positions previously measured for film 1 when laminating with film 1, and the reflection spectrum of each corresponding sample was obtained in the same manner. The correlation coefficient in the range of 400 to 1200 nm was calculated from the reflection spectrum of each corresponding sample, and the correlation coefficient of the reflection spectra of films 1 and 2 was obtained. The maximum correlation coefficient among these was taken as the maximum correlation coefficient of the reflection spectra, and the minimum correlation coefficient was taken as the minimum correlation coefficient of the reflection spectra. The measurement using the spectrophotometer was performed at the center of each sample.

[0079] (3) Average reflectance of visible light A 10 cm square sample was cut from the center of a 50 cm square sheet, and the reflection spectrum was measured in the wavelength band of 400 to 750 nm using the same method as in (2). The average reflectance was calculated by calculating the area enclosed by the reflection curve and the wavelength band based on the Simpson's formula using the absolute reflectance data for every 1 nm of wavelength, and dividing it by 350 nm, which is the width of the wavelength band. The measurement using the spectrophotometer was performed at the center of the sample.

[0080] (4) Color difference Δa measured at an incidence angle of X° * [X°], Δb * [X°] A 50 cm square sheet was divided into 25 equal 10 cm squares, and the reflectance was measured at 25 points at the center of each square area using an integrating sphere attached to a spectrophotometer (U-4100 Spectrophotometer, Hitachi, Ltd.) as a basic configuration. The aluminum oxide secondary white plate attached to the device was used as a reference, and an attached polarizer made by Glan Taylor was installed to measure the reflectance at wavelengths of 380 to 780 nm at an incidence angle Φ = X° with the polarization components set to 0 and 90°. The average value of the measured values ​​for the polarization components 0 and 90° for each wavelength was taken as the reflectance at an incidence angle Φ = X°. The measurement conditions were as follows: measurement wavelength 240 nm to 1750 nm, slit 2 nm (visible) / automatic control (infrared), gain 2, and scanning speed 600 nm / min. Next, from the average spectral reflectance curves for each angle, the color difference Δa measured at an incident angle of X° with D65 light was calculated using the formula specified in JIS Z 8781 (2013). * [X°], Δb * [X°] was calculated.

[0081] (5) Interlayer adhesion In accordance with JIS K5600-5-6 (1999), a cross-cut spacer (manufactured by Cortec Co., Ltd.: Model CROSS CUT GUIDE1.0) and a cutter knife were used to make 6 cuts in the vertical direction and 6 cuts in the horizontal direction at 1 mm intervals on the evaluation specimen (this operation created a grid of 5 x 5 = 25 squares). A transparent pressure-sensitive adhesive tape (manufactured by Nitto Denko Co., Ltd.: Model 31B) was pressed onto the grid, and the number of peeled grids was determined when the pressed tape was peeled off in a direction of approximately 60°. Measurements were performed with N=5, and the average value was used to evaluate according to the following criteria. ○: No peeling occurred in any of the 25 grids (number of peeled off grids was 0 or more but less than 1 grid). △: 1 to 2 grid cells out of 25 cells were peeled off. ×: Two or more of the 25 grids were peeled off.

[0082] (6) Injection moldability The sheet was cut to a predetermined size and set in a mold, and injection molding was performed under the following conditions to produce a molded body. When polycarbonate resin was laminated only on one side of the sheet, the sheet was set in the mold so that the polycarbonate resin layer side was located on the gate side. When polycarbonate resin was not laminated on either side, a binder layer was formed on one side under the following conditions in order to increase adhesion with the injected polycarbonate resin, and the sheet was set in the mold so that the binder layer was located on the gate side. The appearance of the obtained molded body was visually observed and judged according to the following criteria. <Formation of binder layer> Binder: Teikoku Ink Mfg. Co., Ltd. IMB-003 Screen mesh: T-225 Drying: 90℃ x 60 minutes (box drying) <Injection molding> Clamping pressure: 80 tons Mold temperature: 80℃ Molding resin: Teijin Chemical Co., Ltd. polycarbonate resin "Panlite" (registered trademark) 1225L Molding resin temperature: 295℃ Injection speed: 200mm / s Molded product dimensions (L x W x H): 150 x 50 x 2 mm Gate: φ2mm pin gate. <Evaluation criteria> ○: No change in appearance. ×: There is a change in metallic luster at the gate portion.

[0083] [Raw materials] The following materials were used as the raw materials for the sheet. Note that the mixing ratios in the explanation of the raw materials are all mass ratios.

[0084] (Resin A-1) To a mixture of 100 parts by mass of dimethyl terephthalate and 60 parts by mass of ethylene glycol, 0.09 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were added relative to the amount of dimethyl terephthalate, and the mixture was heated and heated in a conventional manner to carry out an ester exchange reaction. Next, 0.020 parts by mass of an 85% aqueous solution of phosphoric acid relative to the amount of dimethyl terephthalate was added to the ester exchange reaction product, and the mixture was then transferred to a polycondensation reaction tank. The reaction system was gradually depressurized while being heated and heated, and a polycondensation reaction was carried out at 290°C under a reduced pressure of 1 mmHg in a conventional manner to obtain polyethylene terephthalate (hereinafter sometimes referred to as PET) having an intrinsic viscosity (IV) of 0.61, which is a crystalline resin.

[0085] (Resin A-2) Polymerization was carried out in the same manner as for Resin A-1, except that a mixture of 100 parts by mass of dimethyl 2,6-naphthalenedicarboxylate and 60 parts by mass of ethylene glycol was used, to obtain a crystalline resin, polyethylene naphthalate (hereinafter sometimes referred to as PEN), having an intrinsic viscosity (IV) of 0.67.

[0086] (Resin B-1) A copolymerized polyethylene terephthalate mixture obtained by mixing polyethylene terephthalate copolymerized with 30 mol% cyclohexanedimethanol (CHDM), an amorphous resin with an intrinsic viscosity (IV) of 0.75, and resin A-1 in an 82:18 ratio.

[0087] (Resin B-2) A copolymerized polyethylene naphthalate mixture made by mixing polyethylene terephthalate copolymerized with 30 mol% cyclohexanedimethanol (CHDM), an amorphous resin with an intrinsic viscosity (IV) of 0.75, and resin A-2 in a 70:30 ratio.

[0088] (Resin B-3) A copolymerized polyethylene terephthalate mixture made by mixing polyethylene terephthalate copolymerized with 30 mol% cyclohexanedimethanol (CHDM), an amorphous resin with an intrinsic viscosity (IV) of 0.75, and resin A-1 in a 62:38 ratio.

[0089] (Resin B-4) A polyethylene terephthalate copolymer mixture obtained by mixing polyethylene terephthalate copolymerized with 21 mol% sproglycol (SPG) and 24 mol% cyclohexanedicarboxylic acid (CHDC), an amorphous resin with an intrinsic viscosity (IV) of 0.60, and Resin A-1 in a ratio of 85:15.

[0090] (Resin B-5) Polyethylene terephthalate copolymerized with 30 mol% cyclohexanedimethanol (CHDM), an amorphous resin with an intrinsic viscosity (IV) of 0.75.

[0091] (Polycarbonate resin film) A polycarbonate resin film "Panlite" (registered trademark) PC-2151 (thickness 125 μm) manufactured by Teijin Limited was used.

[0092] The crystalline / amorphous nature of each resin was determined by heating the resin from 30°C to 300°C at a heating rate of 10°C per minute using a differential scanning calorimeter (DSC) and determining whether or not a crystalline melting point peak was observed in the DSC curve.

[0093] Example 1 Resin A-1 was melted at 290°C as thermoplastic resin A in a single screw extruder, and resin B-1 was melted at 285°C as thermoplastic resin B in a vented twin screw extruder, and then the melted resins were merged in an 801-layer feed block having four separate members with 200 slits through a gear pump and a filter. The outermost layers on both sides of the thick film layer were resin A-1, and resin A-1 and resin B-1 were alternately laminated, and the layer thickness of the adjacent layer made of resin A-1 and layer made of resin B-1 were made to be almost the same. Next, the melt laminate was introduced into a T-die to be molded into a sheet, and then it was brought into contact with a casting drum whose surface temperature was kept at 25°C by applying electrostatic force, and rapidly cooled and solidified to obtain a casting film.

[0094] The obtained casting film was heated with a group of rolls set at 75°C, and then stretched 3.3 times in the machine direction while rapidly heating from both sides with a radiation heater within a stretching section length of 100 mm, and then cooled once to obtain a uniaxially oriented film. Next, a coating liquid for forming an easy-adhesion layer containing (polyester resin with a glass transition temperature of 18°C) / (polyester resin with a glass transition temperature of 82°C) / (silica particles with an average particle size of 100 nm) was applied to both sides of the uniaxially oriented film with a #4 metabar.

[0095] The uniaxially oriented film coated with the coating liquid was introduced into a tenter, preheated with hot air at 100°C, and then stretched 3.5 times in the transverse direction at a temperature of 125°C. The stretched film was heat-treated with hot air at 240°C in the tenter as it was, and then relaxed by 1.5% in the width direction at the same temperature. The film was then cooled to room temperature and wound up with a winder to obtain a film roll. The total thickness of the obtained film was 106 μm. The layer design of this film is as shown in FIG. 1, and the layer thickness of each layer was controlled by adjusting the slit gap. The cross section of the film in the thickness direction was observed with a TEM, and the layer thickness distribution was obtained by image processing. The layer thicknesses of the outermost layers, layer number 1 and layer number 801, were all 6 μm, and the layer thicknesses of layer numbers 201, 401, and 601 composed of resin A-1 were 4 μm. The evaluation results of the obtained film are shown in Table 1.

[0096] The obtained film roll was cut and removed at both ends in the width direction with a slitter, cut in half in the width direction, and wound up, and the two obtained film rolls were laminated so that the top left side of one film roll overlaps the top left side of the other film roll, and the reflection spectrum was measured by the method described in (2) of the evaluation method of various characteristics, and the maximum and minimum values ​​of the correlation coefficient were obtained. Note that, since the reflection spectrum in the longitudinal direction of the film roll obtained by the above method hardly changes, if the position in the width direction of the film roll is the same, the reflection spectrum can be considered to be almost the same.

[0097] Next, a two-component polyurethane thermosetting adhesive (Toyo Ink Co., Ltd. dry lamination adhesive BLS-PC21) was applied to one side of one of the film rolls (film 1) using a reverse gravure coating device at a wet coating amount of 5 g / m. 2 The coating was then applied. After drying at a temperature of 70°C to 90°C and a speed of 20 m / min, the other film (film 2) was laminated, as described above, using nip rolls set at a nip pressure of 0.4 MPa and a temperature of 40°C so that the left side of film 2 overlapped the left side of film 1, to obtain a sheet. The evaluation results of the obtained sheet are shown in Table 1. Note that the "left side of the top unwinding" here refers to the left end viewed from the opposite side of the traveling direction when the film is unwound from the top of the film roll (the left side of the bottom unwinding, described below, can be defined in the same way, except that the film is unwound from the bottom of the film roll).

[0098] (Examples 2 to 4) Films, sheets, and laminates were obtained in the same manner as in Example 1, except that the thermoplastic resins A and B and the number of layers were changed as shown in Table 1. The thicknesses of the outermost layers, layer numbers 1 and 801, were all 6 μm, and the thicknesses of layers 201, 401, and 601 composed of resin A-2 were 4 μm. The evaluation results of the films and sheets are shown in Table 1.

[0099] Example 5 A film, sheet, and laminate were obtained in the same manner as in Example 1, except that the feed block was changed and the layer design of the film was changed to a four-stage gradient of 601 layers. The layer thicknesses of layer numbers 1 and 601, which were the outermost layers, were all 6 μm, and the layer thicknesses of layer numbers 151, 301, and 451 composed of resin A-1 were 4 μm. The evaluation results of the film and sheet are shown in Table 1.

[0100] Example 6 Using a reverse gravure coating device, a two-component polyurethane thermosetting adhesive (Toyo Ink Co., Ltd. dry lamination adhesive BLS-PC21) was applied to one side of the sheet obtained in Example 1 in a wet coating amount of 5 g / m. 2Then, after drying at a temperature of 70° C. to 90° C. and a speed of 20 m / min, the polycarbonate resin film having a thickness of 125 μm was laminated using a nip roll at a nip pressure of 0.4 MPa and a temperature of 40° C. to obtain a laminate. The evaluation results of the obtained laminate are shown in Table 1.

[0101] Example 7 A laminate was obtained by bonding the polycarbonate resin film having a thickness of 125 μm to the surface of the laminate obtained in Example 6 to which the polycarbonate resin film was not bonded, in the same manner as in Example 6. The evaluation results of the obtained laminate are shown in Table 1.

[0102] Comparative Example 1 A film was obtained in the same manner as in Example 1, and a sheet and a laminate were obtained in the same manner as in Example 1, except that films 1 and 2 were laminated so that the lowered left side of film 2 overlapped the uppered left side of film 1. The evaluation results of the film and sheet are shown in Table 1.

[0103] Comparative Example 2 The film was the left roll obtained by cutting in half and winding the film roll of Example 1, and the right roll obtained by cutting in half and winding the film roll of Example 5 was used as Film 2. Films 1 and 2 were laminated together with the top-exposed left sides overlapping each other. Otherwise, a sheet and a laminate were obtained in the same manner as in Example 1. The evaluation results of the film and the obtained sheet are shown in Table 1.

[0104] Comparative Example 3 A film was obtained in the same manner as in Example 1, except that the feed block was changed and the layer design of the film was changed to a four-stage inclination of 401 layers. The layer thicknesses of layer numbers 1 and 401, which are the outermost layers, were both 6 μm, and the layer thicknesses of layer numbers 101, 201, and 301 composed of resin A-1 were 4 μm. The left roll obtained by cutting in half and winding the film roll of Example 1 was used as film 1, and the right roll obtained by cutting in half and winding the film roll of the above 401 layers was used as film 2. Film 1 and film 2 were bonded together so that the left sides of the films were exposed from above and overlapped. A sheet and a laminate were obtained in the same manner as in Example 1 except for the above. The evaluation results of the film and the obtained sheet are shown in Table 1.

[0105] Comparative Example 4 A sheet and a laminate were obtained in the same manner as in Example 1, except that the film of Example 1 was used as film 1, and an 801-layer film obtained in the same manner as in Example 1 except that the thick layers with layer numbers 201, 401, and 601 were not provided as film 2. The evaluation results of the film and the obtained sheet are shown in Table 1.

[0106] Comparative Example 5 Films, sheets, and laminates were obtained in the same manner as in Example 7, except that the thermoplastic resins A and B and the number of layers were changed as shown in Table 1. The thicknesses of the outermost layers, layer numbers 1 and 801, were all 6 μm, and the thicknesses of layers 201, 401, and 601 composed of resin A-1 were 4 μm. The evaluation results of the films and sheets are shown in Table 1.

[0107] Comparative Example 6 The evaluation results of the film 1 of Example 1 alone are shown in Table 1.

[0108] [Table 1] [Industrial Applicability]

[0109] The metallic luster sheet of the present invention has radio wave transmittance, suppresses color variation when viewed obliquely over a large area, and has excellent design properties, making it suitable for use in decorating mirror displays and electric vehicle grilles, for example. [Explanation of symbols]

[0110] 1: Layer number 2: Layer thickness 3: Thickness of the thick film layer 4: Thickness of layer A 5: Thickness of layer B

Claims

1. The average reflectance of visible light from 400 nm to 750 nm when incident perpendicularly to the sheet surface is 40% or more and 80% or less, The color tone value calculated by the formula specified in JIS Z 8781 (2013) using the spectral reflectance measured at an incidence angle of X° relative to the vertical direction of the sheet surface is a * [X°], b * When [X°] is used, a 50 cm square sheet is divided into 25 equal 10 cm squares, and measurements are taken at the 25 centers of each square area, and a is calculated. * [60°] and b * For [60°], a * Difference between maximum and minimum values ​​of [60°] Δa * [60°], and b * Difference between maximum and minimum values ​​of [60°] Δb * [60°] respectively satisfy the following formulas (i) and (ii). Formula (i)Δa * [60°]≦5.0 Formula (ii) Δb * [60°] ≦4.0

2. a * Difference between maximum and minimum values ​​of [30°] Δa * [30°], and b * Difference between maximum and minimum values ​​of [30°] Δb * The sheet according to claim 1, wherein [30°] satisfies the following formulas (iii) and (iv), respectively. Formula (iii) Δa * [30°] ≤ 4.5 Formula (iv) Δb * [30°] ≦ 4.0

3. It is made by laminating two or more films, 3. The sheet according to claim 1 or 2, wherein at least two of the films have a layer (A layer) mainly composed of thermoplastic resin A and a layer (B layer) mainly composed of thermoplastic resin B other than thermoplastic resin A, the A layer and the B layer are alternately positioned in the thickness direction, the total number of the A layers and the B layers is 499 or more, the film has three or more thick film layers having a thickness of 1 μm or more and 20 μm or less, and the thick film layers are the outermost layers on both sides.

4. The sheet according to claim 3 , wherein the layer A and the layer B each contain a crystalline resin.

5. The sheet according to claim 4, wherein the proportion of the crystalline resin in all components constituting the A layer is greater than 15% by mass and less than 100% by mass, and the proportion of the crystalline resin in all components constituting the B layer is 15% by mass or more and 75% by mass or less.

6. A laminate obtained by laminating a layer mainly composed of a polycarbonate resin on the sheet according to claim 1 or 2.

Citation Information

Patent Citations

  • Half-mirror film for display

    JP2016066063A

  • Laminate

    JP2019155621A

  • Multilayer laminated film

    WO2019163891A1